Creativity as a way of being of a nation (persinalistic aspect) - Richard Horban (Cхід, 2019)
The article is devoted to the analysis of the problem of connection between the creative and national aspects in the dimension of the being of the person and the community in the context of national intellectual discourse, which is actual in view of the new wave of existential crisis experienced by modern man. The idea of creativity as an uninterrupted continuum of being of the nation is represented by the concepts of well-known cultural and public figures of the Ukrainian diaspora of the 20th century who represented various fields: cultural studies, study of literature and literary form was represented by Ye.F. Malaniuk, pedagogical and literary forms - by H.H. Vashchenko, church-religious, theological and journalism studies - by S. Yarmus, art studies and art form - by B. Stebelskyi. It is proved that formed on the basis of cordocentric worldview paradigm and, therefore, personalistically and existentially preconditioned, the Ukrainian intellectual thought about the awareness of the ethical value of a person prevailing in Ukrainian ideology is extrapolated from the individual to the ethno-national community. Thus, a nation is regarded as a person. Since personalism implies an active and creative attitude to the world and considers a person as a creative element and a constitutive feature, it is natural that in the context of considering a nation as a common person the problem of ontological communication between the creative and the national one appears. During the last century, Ukrainian intellectual discourse had shaped the idea that the deep psychological needs of the human person are satisfied through creativity, which also justifies its God-likeness, the unique soul of the people is manifested, and most importantly, the spiritual association of all generations of the nation into a holistic personal community is implemented. The author marks the historiosophical concept of Yevhen Malaniuk, who considers the denationalization of the creative sphere of the Eurasian cultural space, which, in turn, led to its depersonalization, the main cause of the crisis of contemporary art. Therefore, within the limits of the examined intellectual discourse the following thought is outlined: the loss of a personal relationship between a creative person and a nation not only leads to a crisis of art and crisis of a personality, but also threatens the existence of a nation. This gives reasons to consider creativity as a way of existence of the nation.